1986
DOI: 10.1203/00006450-198607000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metabolic Intermediate Response following Severe Canine Intrauterine Growth Retardation

Abstract: ABSTRACT. The effect of intrauterine growth retardation and neonatal hypoglycemia on cerebral metabolic intermediates were determined in newborn dogs subjected to 5 days of maternal canine starvation (MCS) before birth.Birth weight was reduced 23% (232 + 6 versus 300 f 10 g). Circulating blood glucose was reduced after 3 h of neonatal fasting in MCS pups (2.7 f 0.4 f versus 5.7 + 1.1 mM). Cerebral cortical levels of glucose were also reduced at this time. Cerebral glucose-6-phosphate was not altered; nonethele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…They ascribed these findings to the absence of hypoxia at the level required to disrupt oxidative metabolism and the energy state of the brain. Kliegman et al (11) demonstrated using a maternal canine starvation model that cerebral charge in FGR neonates was unaffected, whereas their calculated energy reserve was lower than that of controls. Theoretically, depression of oxygen delivery to respiring tissues increases the ADP to ATP ratio (ADP/ATP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They ascribed these findings to the absence of hypoxia at the level required to disrupt oxidative metabolism and the energy state of the brain. Kliegman et al (11) demonstrated using a maternal canine starvation model that cerebral charge in FGR neonates was unaffected, whereas their calculated energy reserve was lower than that of controls. Theoretically, depression of oxygen delivery to respiring tissues increases the ADP to ATP ratio (ADP/ATP).…”
Section: Discussionmentioning
confidence: 99%
“…Manipulations to induce FGR in animal models included surgical ligation of vessels supplying the uteroplacental unit (12) and maternal starvation (11). However, these models do not necessarily reflect the pathophysiology of FGR.…”
Section: F Etal Growth Restriction (Fgr)mentioning
confidence: 99%
See 1 more Smart Citation